DEVELOPMENT STRATEGY OF INTERNATIONAL HUBS BASED ON REGIONAL AIRPORTS IN RUSSIAN FEDERATION - I. A. Belavintsev (Научный вестник МГТУ ГА)
The article deals with an important area of development of the civil aviation airports network and air transport route networks in the Russian Federation and is based on priority development of the largest airport hubs considering the specific characteristics of the current status and further development of internal air transport market and subsidy programs of the Russian regional aircraft.